Iatrogenic genito-urinary fistula following cesarean birth in nine sub-Saharan African countries: a retrospective review - Carrie J. Ngongo; Thomas J. I. P. Raassen; Marietta Mahendeka; Ladeisha Lombard; Jos van Roosmalen (BMC, 2022)
Abstract Background Genito-urinary fistulas may occur as complications of obstetric surgery. Location and circumstances can indicate iatrogenic origin as opposed to pressure necrosis following prolonged, obstructed labor. Methods This retrospective review focuses on 787 women with iatrogenic genito-urinary fistulas among 2942 women who developed fistulas after cesarean birth between 1994 and 2017. They are a subset of 5469 women who sought obstetric fistula repair between 1994 and 2017 in Tanzania, Uganda, Kenya, Malawi, Rwanda, Somalia, South Sudan, Zambia, and Ethiopia. We compared genito-urinary fistula classifications following vaginal birth to classifications following cesarean birth. We assessed whether and how the proportion of iatrogenic genito-urinary fistula was changing over time among women with fistula, comparing women with iatrogenic fistulas to women with fistulas attributable to pressure necrosis. We used mixed effects logistic regression to model the rise in iatrogenic fistula among births resulting in fistula and specifically among cesarean births resulting in fistula. Results Over one-quarter of women with fistula following cesarean birth (26.8%, 787/2942) had an injury caused by surgery rather than pressure necrosis due to prolonged, obstructed labor. Controlling for age, parity, and previous abdominal surgery, the odds of iatrogenic origin nearly doubled over time among all births resulting in fistula (aOR 1.94; 95% CI 1.48-2.54) and rose by 37% among cesarean births resulting in fistula (aOR 1.37; 95% CI 1.02-1.83). In Kenya and Rwanda the rise of iatrogenic injury outpaced the increasing frequency of cesarean birth. Conclusions Despite the strong association between obstetric fistula and prolonged, obstructed labor, more than a quarter of women with fistula after cesarean birth had injuries due to surgical complications rather than pressure necrosis. Risks of iatrogenic fistula during cesarean birth reinforce the importance of appropriate labor management and cesarean decision-making. Rising numbers of iatrogenic fistulas signal a quality crisis in emergency obstetric care. Unaddressed, the impact of this problem will grow as cesarean births become more common.